2021
DOI: 10.1016/j.cmi.2020.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Suspicion of Lyme borreliosis in patients referred to an infectious diseases clinic: what did the patients really have?

Abstract: Objective: To evaluate the conditions behind the symptoms in patients with suspected Lyme borreliosis (LB) who were referred to an infectious diseases clinic. Methods: In this retrospective, population-based study, we collected data from the medical records of all patients referred for infectious disease consultations in 2013 due to presumed LB from a population of 1.58 million. The patients were classified according to the certainty of LB on the basis of their symptoms, signs and laboratory results. Data on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 25 publications
2
9
0
3
Order By: Relevance
“…Patients seeking care at the TBD-RC presented similar epidemiological and clinical characteristics to those in other studies in other settings describing a multidisciplinary care organization for suspected LB [ 27 , 28 , 29 , 30 ]. As previously found in these studies, ~10–20% of suspected cases had confirmed LB.…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…Patients seeking care at the TBD-RC presented similar epidemiological and clinical characteristics to those in other studies in other settings describing a multidisciplinary care organization for suspected LB [ 27 , 28 , 29 , 30 ]. As previously found in these studies, ~10–20% of suspected cases had confirmed LB.…”
Section: Discussionsupporting
confidence: 57%
“…Few patients (9%) had no specific diagnoses compared to other studies varying from 12.1% to 38.5% [ 27 , 28 , 29 , 30 ], probably because they had a regular follow-up in the adapted care sector since the beginning of their management, which allowed for clinical re-evaluations and the confirmation of the diagnosis for a longer period. For patients that have experienced diagnostic delay or serial misdiagnosis, a multidisciplinary approach could be a major answer, helping with acceptance of the diagnosis and offered care [ 23 ].…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations